Participatory Variety Selection and Seed Multiplication of Cereal and Legume Crops in North Shoa and Hadiya Zones, Ethiopia - Bishaw, Zewdie; Aynewa, Yetsedaw; Kemal, Seid Ahmed; Alene, Temesgen (International Center for Agricultural Research in the Dry Areas, 2024)
The highlands of North Shoa in Amhara and Hadiya in Central Ethiopia Regions are dominated by mixed farming systems where cereals (wheat, barley, and tef) followed by food legumes are major crops. The productivity of cereals and food legumes is low due to biotic and abiotic factors and insufficient input supplies like certified seeds, inoculants, and other inputs (Belachew et al. 2022). Because of diseases, insect pests, soil acidity, and water logging problems, farmers are reducing food legume crops area and growing more cereals leading to low crop diversity that plays a role in reduced soil fertility, incomes, rust outbreaks and diet diversity (Tamrat et al. 2023). Several cereal and food legume varieties are released by many centres but many did not reach farmers due to limited demonstration to create awareness and demand and shortage of quality early generation seeds. The limited access to quality seeds contributes to low crop productivity and diversity.